Age-Related Midbrain Inflammation and Senescence in Parkinson’s Disease - Russo, Taylor; Riessland, Markus (Frontiers in Aging Neuroscience, 2022)
Immune responses are arising as a common feature of several neurodegenerative diseases, such as Parkinson’s disease (PD), Alzheimer’s disease (AD), and Amyotrophic Lateral Sclerosis (ALS), but their role as either causative or consequential remains debated. It is evident that there is local inflammation in the midbrain in PD patients even before symptom onset, but the underlying mechanisms remain elusive. In this mini-review, we discuss this midbrain inflammation in the context of PD and argue that cellular senescence may be the cause for this immune response. We postulate that to unravel the relationship between inflammation and senescence in PD, it is crucial to first understand the potential causative roles of various cell types of the midbrain and determine how the possible paracrine spreading of senescence between them may lead to observed local immune responses. We hypothesize that secretion of pro-inflammatory factors by senescent cells in the midbrain triggers neuroinflammation resulting in immune cell-mediated killing of midbrain dopaminergic (DA) neurons in PD.